04 RISIKO PRODUKSI DAN FAKTOR PRODUKSI YANG MEMPENGARUHI USAHATANI PADI PADA LAHAN SAWAH TADAH HUJAN KELURAHAN SOREANG KECAMATAN LAU KABUPATEN MAROS - Jurnal Agribis; Nurlinda Nurlinda; Arifin Arifin; Mohammad Anwar Sadat (Universitas Muslim Maros, 2020)
The main risks of rice farming include frequency, flooding, drought and pest attack, which is currently becoming an increasingly complex problem in the climate change situation. which is difficult to predict because of the need to continue to supply enough rice for the community to consume. Most of the paddy rice farmers are mostly included in the category of subsistence farmers, because farming activities are carried out not only for commercialization purposes but also to fulfill their household food needs. This research was carried out in Soreang Village, Lau District, Maros Regency. In this study aims to determine the factors of production that affect the risk of production of rice farming in the rainfed lowland rice fields Kelurahan soreang, Lau District, Maros Regency. This research was carried out in January to May 2019. The data technique was used with multiple regression techniques. The results of this study affected the production results, land area and experience, while education influenced how to produce production and technological tools in rice in Soreang Village, Lau District, Maros Regency. And as for the production of rice farming in rain-fed rice fields, amounting to Rp. 1.09339767.